Prismatic Effects of lseikonic Spectacle-Contact Lens - Remole, A (Canadian Journal of Optometry, 2021)
The method of correcting aniseikonia in unilateral aphakia by means of a spectacle-contact lens combination has been described in detail in the literature. This article addresses one consequence of such corrections, namely, the induced prismatic effect. A comprehensive formula is developed to show how this effect compares with the aniseikonia corrected.